2002
DOI: 10.3732/ajb.89.6.908
|View full text |Cite
|
Sign up to set email alerts
|

Apical organization and maturation of the cortex and vascular cylinder inArabidopsis thaliana (Brassicaceae) roots

Abstract: Developmental and physiological studies of roots are frequently limited to a post-germination stage. In Arabidopsis, a developmental change in the root meristem architecture during plant ontogenesis has not previously been studied and is addressed presently. Arabidopsis thaliana have closed root apical organization, in which all cell file lineages connect directly to one of three distinct initial tiers. The root meristem organization is dynamic and changes as the root ages from 1 to 4 wk post-germination. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
123
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 39 publications
6
123
0
3
Order By: Relevance
“…The size of the nakr1-1 root meristem region decreased dramatically during the first 7 DAG as determined by analysis of propidium iodidestained roots using confocal microscopy ( Figures 10A and 10C). In comparison, meristem size remained more stable in wild-type seedlings ( Figures 10A and 10C), and a decrease in the number of meristematic cells does not occur in wild-type Arabidopsis until 3 to 4 weeks after germination (Baum et al, 2002). The elongation zone of nakr1-1 seedlings at 7 DAG was typically reduced to three cells in length ( Figure 10A).…”
Section: Mainly By Shoot Defectsmentioning
confidence: 97%
“…The size of the nakr1-1 root meristem region decreased dramatically during the first 7 DAG as determined by analysis of propidium iodidestained roots using confocal microscopy ( Figures 10A and 10C). In comparison, meristem size remained more stable in wild-type seedlings ( Figures 10A and 10C), and a decrease in the number of meristematic cells does not occur in wild-type Arabidopsis until 3 to 4 weeks after germination (Baum et al, 2002). The elongation zone of nakr1-1 seedlings at 7 DAG was typically reduced to three cells in length ( Figure 10A).…”
Section: Mainly By Shoot Defectsmentioning
confidence: 97%
“…Baum et al (2002) discovered that as the root ages, however, a third layer of ground tissue, namely MC, arises from periclinal divisions of the endodermal cells located at the basal region of the root meristem. While the physiological function of MC remains elusive, the follow-up studies have demonstrated that MC formation can be used as a powerful experimental model for the understanding of how developmental patterns are created and maintained in plants (Paquette and Benfey, 2005;Long et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these tissues has typically a single cell layer at early seedling stage. A middle cortex (MC) layer, however, will form as the root ages (Baum et al, 2002). This extra layer is produced via periclinal divisions of the endodermal cells situated a small distance basal from stem cells of the cortex and endodermis.…”
mentioning
confidence: 99%
“…Under our conditions, by d14 a third layer of ground tissue, termed the middle cortex (Baum et al, 2002), begins to form (34% of primary root meristems at d14 had at least one middle-cortex cell, n 5 50). At later time points generation of this layer is apparently maintained by a specific set of divisions of the inner ground tissue stem cell (previously the endodermal stem cell) and its derivatives (Baum et al, 2002).…”
Section: Initiation Of Middle-cortex Formation and Molecular Identitymentioning
confidence: 99%
“…In fact, as the Arabidopsis root ages, a third layer of ground tissue forms, which rapidly takes on cortex character. Baum et al (2002) first reported progressive changes over time in the Arabidopsis root meristem cytoarchitecture. These changes occur later than the early post-embryonic stage that is commonly analyzed in developmental-genetic studies.…”
mentioning
confidence: 99%